1994
DOI: 10.1128/mcb.14.2.1171
|View full text |Cite
|
Sign up to set email alerts
|

Physical and functional interaction between wild-type p53 and mdm2 proteins.

Abstract: The mdm2 oncogene, which is often amplified in mammalian tumors, produces a number of transcripts that encode distinct protein forms. Previous studies demonstrating that overexpression of the mdm2 gene can activate its transforming potential, and can inhibit the transcriptional activation function of p53, prompted us to begin to explore possible functional differences among the various mdm2 products. Utilizing a transient transfection assay, we have evaluated four naturally occurring murine mdm2 forms for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 40 publications
1
100
0
Order By: Relevance
“…Measurement of MDM2-P2 transcript was performed by RNase protection as described (Bull et al, 1998) with cellular RNA isolated from the p53 mutant lines Molt4 (M), HEL (H), CEM (C), Jurkat (J), and Raji (R). All hybridization reactions included a smaller probe complementary to the glyceraldehyde-phosphate-dehydrogenase (GAPDH)`housekeeping' gene to control for potential variability in sample processing H1299 cells were transfected with varying amounts of wt p53 and the R213Q mutant and 3 mg of the Y234H mutant and the pCEP Vector as described previously (Haines et al, 1994) (V). Fortyeight hours after transfection, protein extract was prepared and the amount of MDM2 and p53 protein was measured by a Western blot as described previously (Pan and Haines, 1999).…”
Section: Abstract: P53; Mdm2; P53 Target Genesmentioning
confidence: 99%
“…Measurement of MDM2-P2 transcript was performed by RNase protection as described (Bull et al, 1998) with cellular RNA isolated from the p53 mutant lines Molt4 (M), HEL (H), CEM (C), Jurkat (J), and Raji (R). All hybridization reactions included a smaller probe complementary to the glyceraldehyde-phosphate-dehydrogenase (GAPDH)`housekeeping' gene to control for potential variability in sample processing H1299 cells were transfected with varying amounts of wt p53 and the R213Q mutant and 3 mg of the Y234H mutant and the pCEP Vector as described previously (Haines et al, 1994) (V). Fortyeight hours after transfection, protein extract was prepared and the amount of MDM2 and p53 protein was measured by a Western blot as described previously (Pan and Haines, 1999).…”
Section: Abstract: P53; Mdm2; P53 Target Genesmentioning
confidence: 99%
“…For example, IR generates single-and double-strand DNA breaks and oxidative base damage. Recent studies have suggested that the ataxia telangiectasia gene (ATM) plays a crucial role in detecting DNA damage induced by IR and signaling to activate p53 (McKinnon, 1987;Canman et al, 1994;Haines et al, 1994;Meyn, 1995). ATM also participates in the UV pathway, since AT cells are unable to induce the G1 checkpoint after UV radiation (Kaufmann and Wilson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Full length Mdm2 protein, as well as several smaller forms thereof (Olson, 1993), bind to p53. This binding renders p53 biochemically inactive, and also targets it for rapid degradation within the cell (Momand et al, 1992;Wu et al, 1993;Haines et al, 1994;Oliner et al, 1993;Barak et al, 1993;Zauberman et al, 1993;Chen et al, 1995;Haupt et al, 1997;Kubbutat et al, 1997). Thus, activation of mdm2 gene expression by p53 probably drives a negative feedback loop, whereby cellular p53 activity is kept in check and the p53 signal is properly terminated (Wu et al, 1993;Barak et al, 1993;Picksley and Lane, 1993;Momand and Zambetti, 1997).…”
Section: Introductionmentioning
confidence: 99%